The potential use of melatonin for preventing cisplatin ototoxicity : an insight for a clinical approach - Araujo, Juliana Gusmão de (2014)
Cisplatin, one of the most effective and potent anticancer drugs, is used in the treatment of a wide variety of both pediatric and adult malignancies. However, the chemotherapeutic use of cisplatin is limited by its serious side effects, such as nephrotoxicity and ototoxicity. Ototoxicity produced by cisplatin is usually persistent, depending on the age of the patient, the cumulative number of doses, the number of chemotherapy cycles, the history of noise exposure, and deteriorating renal function. The mechanism of the ototoxicity caused by cisplatin is based on the generation of reactive oxygen species, which interfere with the antioxidant protection of the organ of Corti. Thus, protecting the cochlea with antioxidants ameliorates ototoxicity from cisplatin. In this context, melatonin appears as a therapeutic option for preventing the ototoxic effects of cisplatin, since the research in the last decade has proven its ability to be both a direct free radical scavenger and indirect antioxidant. In this sense, some of the evidence suggesting that melatonin is efficient for combating cisplatin-induced ototoxicity is summarized and discussed in this paper.